Comparison of the Accuracy of Intraoral Scanners Based on the Type of Tooth Preparation for a Single Crown - Dong-Geun Lee; Keunbada Son; Kyu-Bok Lee (Applied Sciences, 2021)
The purpose of this study was to evaluate the accuracy of intraoral scanners in 10 abutments (five premolars and five molars) obtained in a dental clinic and to analyze the impacts of the volume and area of abutments on scanning accuracy. Abutment casts were scanned five times with a 3D contact scanner (DS10; Renishaw plc). The five scan files were lined up and then merged, and one high-resolution computer-aided design reference model (CRM) was obtained. To obtain a computer-aided design test model (CTM), three types of intraoral scanners (CS3600 (Carestream Dental), i500 (Medit), and EZIS PO (DDS)) and one type of laboratory scanner (E1; 3Shape) were employed. Using 3D analysis software (Geomagic control X; 3D Systems), the accuracy of the scanners was evaluated, including optimal overlap by optimal alignment. The conformity of the overlapped data was calculated by the root mean square (RMS) value, using the 3D compare function for evaluation. As for statistical analysis, testing was conducted, using one-way and two-way ANOVA and the Tukey HSD test (α = 0.05) for the comparison of the groups. To analyze the correlations of the volume and area of the abutments with accuracy, Pearson’s correlation analysis was conducted (α = 0.00625). Both premolar and molar abutments showed a lower RMS value on the laboratory scanner than on the intraoral scanners, and the RMS value was lower in premolars than in molars (p < 0.001). In the intraoral scanner group, CS3600 showed the best accuracy (p < 0.001). There were significant positive correlations for the volume and area of the abutments with accuracy (p < 0.001). The type, volume, and area of the clinically applicable abutments may affect the accuracy of intraoral scanners; however, the scanners used in the present study showed a clinically acceptable accuracy range, regardless of the type of abutment.